Pelatihan Pengemasan Paket Wisata Olahraga di Kampung Wisata Titik Nol Jateng - Indri Kurniawati; Ebtana Sella Mayang Fitri; Ajie Wicaksono (Lembaga Pengembangan Kinerja Dosen, 2026)
Kampung Wisata Titik Nol in Central Java has significant potential for developing special-interest tourism, particularly nature-based and outdoor sport tourism. However, this potential has not been optimally utilized due to limited community capacity in designing structured and market-ready tourism products. This community service program aims to enhance the capacity of local tourism managers and youth organizations in packaging sustainable and competitive sport tourism packages. The program was conducted at Joglo Gumregah from August to November 2024 using a Participatory Action Research (PAR) approach. The implementation was carried out in three phases: preparation, implementation, and evaluation. The preparation phase included field observation, Focus Group Discussions (FGDs), and coordination with village authorities and community leaders. The implementation phase involved in-depth interviews and mentoring activities in developing sport tourism packages. The evaluation phase was conducted through interactive dialogues with stakeholders to refine the developed packages. The results indicate an improvement in participants’ understanding and skills in designing integrated and locally based sport tourism packages. The resulting packages are expected to serve as references for sport tourism development and to support community empowerment and economic sustainability in Kampung Wisata Titik Nol.